Simulation of the BLT (Direct Cash Assistance) Distribution Queue with the Exponential method - Irfan Jaya; Imran Lubis; Marto Sihombing (International Journal of Health Engineering and Technology, 2022)
Queues are part of everyday human life. Queues occur when the number of customers to be served exceeds the capacity of an available service. This queuing situation can be found in several incidents, one of which is the queuing system at the Cash Direct Assistance (BLT) reception counter. Problems that often occur in receiving Direct Cash Assistance (BLT) at the village office are often queuing for more than 15 people to collect cash transfers, plus irregular queuing makes officers confused to serve the community, even sudden cancellations occur because of the short time. very limited and cut off when the officers rested at lunch time, which made several other people who had not been served annoyed and disappointed when they had to queue for a very long time, they had to come back tomorrow and queue again, causing public discomfort to services at the village office. Therefore, it is urgently needed a queuing system that is carried out to prevent prolonged queues in the distribution of BLT (Direct Cash Assistance) in the village, so that people who take BLT funds do not wait long enough and are more regular in queuing.